Effectiveness of personalized continuous care in wound care of patients with diabetic foot ulcers - Mi, Yan; Wang, Jing (Frontiers in Endocrinology, 2025)
BackgroundDiabetic foot ulcers (DFUs), a common complication of diabetes, are often accompanied by delayed wound healing, pain, psychological distress, and sleep disturbances.ObjectiveTo evaluate the effectiveness of personalized continuous care (PCC) compared to routine care in improving wound healing, symptom severity, and psychological/sleep outcomes in DFU patients.MethodsA retrospective cohort study of 60 DFU patients (2021–2024) compared PCC (n=30) with routine care (n=30). Outcomes assessed included wound area reduction, granulation tissue coverage, symptom scores (ulceration, necrosis, pain), and validated psychological (SDS, SAS) and sleep (AIS) scales.ResultsThe PCC group showed superior wound healing (40.51% vs. 27.43% area reduction; 61.66% vs. 46.32% granulation coverage, p<0.05), lower symptom scores (ulceration: 3.18 ± 0.45 vs. 4.46 ± 0.6; pain: 2.01 ± 0.29 vs. 3.45 ± 0.58, p<0.01), and improved psychological (SDS: 32.1 ± 3.88 vs. 44.87 ± 4.05; SAS: 30.36 ± 3.77 vs. 43.25 ± 4.56, p<0.001) and sleep outcomes (AIS: 8.23 ± 0.6 vs. 11.33 ± 0.94, p<0.001).ConclusionPCC enhances DFU wound healing, alleviates symptoms, and improves psychological well-being and sleep quality, supporting its integration routine clinical practice.